How to guide your team through change (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Nothing is certain except death, taxes, and change. Change is inevitable, it comes for us in all aspects of our lives, and when you're managing a team, you are watching it affect not only yourself but also those who work around you. In this audio course, we teach you how to help you manage change effectively, how to motivate and guide your team through change. Learning Objectives Learn what your role is as a manager during a transition Learn what you must and must not do in order to make the transition process more comfortable for your team Learn important communication techniques to ensure change programs work smoothly.